In vitro interactions between several species of harmful algae and haemocytes of bivalve molluscs - Hegaret, Helene; da Silva, Patricia Mirella; Wikfors, Gary, H.; Haberkorn, Hansy; Shumway, Sandra, E.; Soudant, Philippe (Cell Biology and Toxicology, 2011)
International audience Harmful algal blooms (HABs) can have both lethal and sublethal impacts on shellfish. To understand the possible roles of haemocytes in bivalve immune responses to HABs and how the algae are affected by these cells (haemocytes), in vitro tests between cultured harmful algal species and haemocytes of the northern quahog (= hard clam) Mercenaria mercenaria, the soft-shell clam Mya arenaria, the eastern and Pacific oysters Crassostrea virginica and Crassostrea gigas and the Manila clam Ruditapes philippinarum were carried out. Within their respective ranges of distribution, these shellfish species can experience blooms of several HAB species, including Prorocentrum minimum, Heterosigma akashiwo, Alexandrium fundyense, Alexandrium minutum and Karenia spp.; thus, these algal species were chosen for testing. Possible differences in haemocyte variables attributable to harmful algae and also effects of haemolymph and haemocytes on the algae themselves were measured. Using microscopic and flow cytometric observations, changes were measured in haemocytes, including cell morphology, mortality, phagocytosis, adhesion and reactive oxygen species (ROS) production, as well as changes in the physiology and the characteristics of the algal cells, including mortality, size, internal complexity and chlorophyll fluorescence. These experiments suggest different effects of the several species of harmful algae upon bivalve haemocytes. Some harmful algae act as immunostimulants, whereas others are immunosuppressive. P. minimum appears to activate haemocytes, but the other harmful algal species tested seem to cause a suppression of immune functions, generally consisting of decreases in phagocytosis, production of ROS and cell adhesion and besides cause an increase in the percentage of dead haemocytes, which could be attributable to the action of chemical toxins. Microalgal cells exposed to shellfish haemolymph generally showed evidence of algal degradation, e.g. loss of chlorophyll fluorescence and modification ...